2014
DOI: 10.1016/j.jjcc.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between left atrial features in well-controlled hypertensive patients and normal subjects assessed by three-dimensional speckle tracking echocardiography

Abstract: These results suggest that LV diastolic dysfunction occurs before structural changes of left atrium and left ventricle even in patients with well-controlled HTN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…However, another Chinese cross-sectional study reported that these three function of LA all impaired in HT group [33] . Disparities among these reports may be result from different grade of HT, age, duration of HT, grade of HT, medication and the control of blood pressure [34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…However, another Chinese cross-sectional study reported that these three function of LA all impaired in HT group [33] . Disparities among these reports may be result from different grade of HT, age, duration of HT, grade of HT, medication and the control of blood pressure [34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…LA enlargement and dysfunction are frequently seen in patients with PAF and HT, thus increasing cardiovascular risk and becoming indexes of future cardiovascular events 32,33 . Several studies investigate LA function in terms of shape parameters or 2D strain, but often they evaluated this in a single moment of the entire atrial cycle; moreover, they considered only control subjects versus AF patients 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in echocardiographic imaging and mainly the advent of two-dimensional speckle tracking echocardiography (2D-STE) myocardial strain assessment enabled a more independent insight into atrial function by visualising and calculating each of the phases separately [ 4 ]. Alterations in 2D-STE-derived atrial strain assessment have already been described in patients with systemic arterial hypertension [ 5 , 6 ], atrial fibrillation [ 7 ] and diastolic heart failure [ 8 ]. Indeed, this non-invasive tool holds promise for detecting even subclinical stages of atrial dysfunction [ 9 ] which would enable initiation of therapy before irreversible atrial damage occurs and thereby has important clinical implications for the evaluation and management of patients with various cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%